INVARIAN AUTOMATIC CONTROL SYSTEM, USING THE INTERMEDIATE-FREQUENCY SIGNALS OF HEAT POWER PARAMETERS - G. T. Kulakov; A. N. Kukhorenko; I. M. Golinko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The usage of digital micro-processing automatic means allow to use design methods (technique) of automatic control systems  more wider, and also to apply optimal ways of control, for example, it is possible to combine the Method of structural-parameter optimization and invariance theory. This method allow to increase essential system speed in processing of task jump and to reduce operation time of outside external disturbance up to two  values of regulated influence, and the usage of invariance principle is based on an additional measuring of the most dangerous perturbation influence and in connection with it the improvement of regulation quality is achieved.In this article the principle of invariance is applied in order to improve greatly external disturbance attack by consumption of over-heated steam. Compensation of disturbance influence on regulated value is achieving by introduction of additional signal on input of correction regulator from output of compensation device, measuring the external disturbance by consumption of over-heated steam.Modeling results of transient processes of cascade system of automatic control (CSAC), on the base of which were realized the unity of these methods, demonstrated the fact that, in processing of external disturbance by consumption of steam, the reduction of maximal dynamic regulation error is six times and cutting of regulation time by 30 % in comparison with CSAC without compensation device of external disturbance. And that is why it leads to the further reduction of maximal dynamic regulation error in processing of external disturbance by consumption of steam, and this allows to improve the quality of control.